Direitos Humanos, gênero, cidadania e educação - Brabo, Tânia Suely Antonelli Marcelino (Editora Oficina Universitária, 2022)
Over these twenty-four years of activities in Marília and region, in the academic field, NUDHUC has been dedicated to training, production of publications and guidance of research, intending to promote critical reflection and deepen knowledge about education in human rights , gender, race/ethnicity, citizenship, among other topics. After holding the scientific events, always aiming to remember the history of the struggle to guarantee the rights of all people in the history of our country and of humanity, so that the new generations get to know it and reflect on the value of freedom, human rights, of respect and dignity for all people, values of Democracy, texts originating from the events have been published. In this perspective, in this collection, we have the participation of researchers and activists defending Human Rights from Argentina, Spain and Brazil who have dedicated themselves to recording History, analyzing, from a general point of view, through Sociology , Psychology and Education, the conditions for advances and setbacks with regard to the guarantee of Human Rights, to think about the current challenges that are posed at a time when we see actions by conservative groups organizing themselves for the approval of projects such as the School without a Party, in addition to attacks on human rights and their defenders, who show resistance by giving an example of exercising full citizenship.